Development of time perspective in nenets, Sami and Russian adolescents: A comparative analysis - Flotskaya, Natalia; Aryabkina, Irina; Bulanova, Svetlana; Ponomareva, Maria; Flotskiy, Nikolay (Amazonia Investiga, 2023)
This paper is concerned with the issue of studying specific features of the development of time perspective in adolescents representing different ethnic groups living in the North of Russia. The study includes a comparative analysis of the development of time perspective in Nenets, Sami, and ethnic Russian male and female adolescents. The current article presents the results of an empirical study conducted using the Zimbardo Time Perspective Inventory. The respondents in the empirical study were 99 Nenets adolescents aged 12-15 years (54 boys and 45 girls); 79 Sami adolescents aged 12-15 years (41 boys and 38 girls); 121 ethnic Russian adolescents aged 12-15 years (63 boys and 58 girls). The comparative analysis of the development of time perspective in Nenets, Sami, and ethnic Russian adolescents has shown the presence of similar trends characteristic of the age group in general, and specific features at the same time. The results of the study enrich the scientific understanding of the phenomenon of time perspective, supplement and expand the understanding of the process of personality formation in representatives of different ethnic groups living in the North of Russia. The identified features of time perspective in adolescents will help to supplement the programs of psychological assistance and support for adolescents in the aspect of building life strategies, implementing capabilities of forecasting life prospects and managing time resources.